The first session is the one that counts: An exploratory study of therapeutic alliance - del Río Olvera, Francisco Javier; Rodríguez-Mora, Álvaro; Senín-Calderón, Cristina; Rodríguez-Testal, Juan F. (Frontiers in Psychology, 2022)
Background The controversy about whether psychotherapy outcome is the consequence of the techniques themselves, common factors or both is still current. The importance of common factors has been demonstrated, although it is also known that they alone are insufficient. At the present time, the contextual model grants heavy weight to the therapeutic alliance in the first sessions and seems to predict positive final results. Furthermore, monitoring sessions has demonstrated that this alliance improves. Objectives To analyze the relationship between the therapeutic alliance and patient’s perceived improvement during the first five sessions of therapy, and find out whether the therapeutic alliance is maintained or unstable within that timeframe. Methods Thirty-four patients at a university psychological care service who had had at least five therapy sessions participated. Of these, 70.46% were women (Mage = 24.24, SD = 6.73). The patients filled out the Outcome Rating Scale and Session Rating Scale the week before each session. Data were analyzed by the Dual STATIS method. Results The compromise matrix explained 77.36% of the variability. The position of the vectors and the distribution of the position of the patients on the graph show that as their perception increased, therapeutic alliance remained stable. Moreover, the position of the vectors shows that the therapeutic alliance was forged in the first session and remained stable during the following sessions. Conclusion This exploratory study demonstrated the importance of the first session in establishing the therapeutic alliance, and for it to remain stable, regardless of whether the rest of the therapeutic process has variations or changes. Novel use of the STATIS method for analyzing measurements in the first five sessions, showed that beginning the therapeutic intervention with a strong alliance, produced the favorable, lasting effects necessary for development of the intervention.